Heaven Is a Beautiful Place : A Memoir of the South Carolina Coast - Peterkin, Genevieve C. (Genevieve Chandler), 1928-2011 (Book collections on Project MUSE., 2000)
The author, Genevieve "Sister" Peterkin, tells the tales of her talented mother, Genevieve Willcox Chandler; her "second mother," Lillie Knox; her mother-in-law, Julia Mood Peterkin; and of growing up in Murrells Inlet, South Carolina